Pengaruh Pemberian Biourine Sapi Terhadap Pertumbuhan dan Hasil Tanaman Bayam (Amaranthus spp.) Sistem Hidroponik - Dominikus Bulu Bili; I Putu Sujana; Ni Putu Pandawani (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This study entitled "The Effect of Cattle Biourine on Growth and Yield of Green Spinach (Amaranthus spp) in Hydroponic Systems. The hydroponic method used in this research is the wick system. The research implementation stage was using a randomized block design (RBD) of 6 treatments and 4 replications of biourinesapi, consisting of 6 treatments and 4 replications in order to obtain 24 treatments. The results of this study indicate that the provision of biourine 300 ml / liter of water is sufficient to provide good growth and yield of spinach, although with the increase in the growth of bovine biourine to 600 ml / 1 liter of water, there is no significant increase in growth and yield. The difference in biourin administration is giving 100 ml / 1 liter of water; giving 200 ml / 1 liter of water; giving 300 ml / 1 liter of water; giving 400 ml / 1 liter of water; giving 500 ml / 1 liter of water and giving 600 ml / 1 liter of water to spinach plants with a hydroponic system had a significant effect on the growth and yield of spinach plants, the highest growth and yield of spinach in the hydroponic system was obtained by administering biourin by administering cow biourine. 600 ml / 1 liter of water but not significantly higher than the growth and yield of spinach in the administration of 300 ml / 1 liter of water, 400 ml / 1 liter of water; 500 ml / 1 liter of water, giving 300 ml / 1 liter of bovine biourine is the right provision to provide the best growth and yield of spinach on hydroponic systems compared to higher and lower yields